Respuesta :

Good morning ☕️

Answer:

[tex](\frac{-2}{3} , -2)[/tex]

Step-by-step explanation:

3x+y=-4   (1)

3x-4y=6  (2)

solving by elimination:

(1) - (2) ⇒

3x + y  = -4

3x - 4y = 6

________

0 + 5y  = -10

5y = -10 ⇔ y = -2

(2) ⇒ 3x-4y=6  ⇒ 3x-4(-2)=6  ⇒ 3x = 6 - 8 = -2 ⇒ x = -2/3

___________________________________________

:)

Answer: x = 2, y = -2

Step-by-step explanation:

Subtract the two equations:

3x+y=-4......equation 1

3x-4y=6.......equation 2

5y = -10

Divide both sides by 5 to get the value of y

y = -2

Insert the value of y into equation 1 to get the value of x

3x + y = -4

3x + (-2) = -4

3x -2 = 4

3x = 4 +2

3x = 6

Divide both sides by 3 to get the value of x

x = 6/3

x = 2

Check: insert the values of x and y into equation 1

3x + y = 4

3 (2) + (-2) = 4

6 - 2= 4

I hope this is clear, please mark as brainliest answer.